Enhancing The Maharah Istima' Using Inquiry Strategy and Audio Media - Lubis, Arbonas; Fian Triadi; Shidiq, Abdul Aziz (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2023)
The objective of this research is to determine the correlation The objective of this study is to establish the correlation between the use of audio media and maharah istima'. The research methodology employs a correlational approach, focusing on the population of first semester students enrolled in the Islamic Religious Education study programme at As-Sunnah Deli Serdang Islamic College. The total number of students in this population is 23. The data collection methods employed surveys for auditory usage and tests for listening skills. The data analysis approaches utilised normality, homogeneity, and product moment tests with the assistance of SPSS. The research findings indicate that the utilisation of audio media is rather common, accounting for 39% of the total, but the proficiency in listening skills, known as "maharah istima'", is relatively poor, with a score of 75%. There is no correlation between the utilisation of audio media for maharah istima' and the statistical computations' outcome of a product moment of -0.043, as indicated by the significance value in the Sig column. The two-tailed p-value of 0.844 is greater above the significance level of 0.05.